Antibacterial, ester-free monomers: Polymerization kinetics, mechanical properties, biocompatibility and anti-biofilm activity. (December 2019) - Fugolin, Ana P.; Dobson, Adam; Huynh, Vincent; Mbiya, Wilbes; Navarro, Oscar; Franca, Cristiane M.; Logan, Matthew; Merritt, Justin L.; Ferracane, Jack L.; Pfeifer, Carmem S.
Abstract: Objectives: Quaternary ammonium (QA) methacrylate monomers have been extensively investigated and demonstrate excellent antibacterial properties. However, the presence of ester bonds makes them prone to degradation in the oral cavity. In this study, ester-free QA monomers based on meth-acrylamides were synthesized and screened for polymerization kinetics, mechanical properties and antibacterial effects. Materials and methods: Tertiary quaternary ammonium acrylamides (AM) and methacrylamides (MAM) with alkyl side chain lengths of 9 and 14 carbons (C9 and C14) were synthesized and incorporated at 10 wt% into experimental composites based on BisGMA:TEGDMA (1:1), camphorquinone/ethyl-4-dimethylaminobenzoate (0.2/0.8 wt%) and 70 wt% barium glass fillers. Analogous methacrylate versions (MA) were used as controls. Degree of conversion (DC) and rate of polymerization (RP) during photoactivation (800 mW/cm 2 ) were followed in real-time with near-IR. Flexural Strength (FS) and Modulus (E) were measured on 2 × 2 × 25 mm bars in 3-point bending after 24 h dry storage and 7-day storage in water at 37 °C. Antimicrobial properties and biofilm adhesion (fouling) were evaluated by bioluminescence (Luciferase Assay) and biofilm removal by water spray microjet impingement test, respectively. Cytotoxicity was assessed by MTT assay on dental pulp stem cells (DPSC). Data were analyzed with one-way ANOVA/Tukey's test (α = 0.05). Results: DC was similar for all groups tested (∼70%). Both MAMs and C14-AM presented significantly lower RP. Under dry conditions, FS (110–120 MPa) and E (8–9 GPa) were similar for all groups. After water storage, all materials presented FS/E similar to the control, except for C14-AM (for FS) and C14-MAM (for E), which were lower. All C14 versions were strongly antibacterial, decreasing the titer counts of biofilm by more than two orders of magnitude in comparison to the control. C9 monomers did not present significant antibacterial nor antifouling properties. And biofilms had approximately equivalent adhesion on the C9 composites as on the control. Cytotoxicity did not show significant differences between the MA and AM versions and the control group. Conclusions: C14-QA monomers based on methacrylates and meth-acrylamides present strong antibacterial properties, and in general, similar conversion/mechanical properties compared to the methacrylate control. Statement of Significance: This work demonstrates the viability of methacrylamides and acrylamides as potential components in dental restorative materials with antimicrobial properties. The use of ester-free polymerizable functionalities has the potential of improving the degradation resistance of these materials long-term. The use of (meth)acrylamides did not interfere with the antimicrobial potential of quaternary ammonium-based materials. Graphical abstract: Image, graphical abstract